Pelatihan Aplikasi Pixton dalam Mengembangkan Media Graphic Novel untuk Meningkatkan Kreativitas dan Literasi Digital Guru TK Pertiwi Sowan Kidul - Dina Amalia; Aliva Rosdiana; Olyvia Revalita Candraloka; Fitria Firdasari; Nistu Maulana Zainul Anan (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the creativity and digital literacy of kindergarten teachers through training in graphic novel learning media based on the Pixton application. The program was implemented using a participatory approach grounded in continuous mentoring, involving 10 teachers from TK Pertiwi Sowan Kidul, Jepara Regency, as partners. Evaluation instruments consisted of pre-test and post-test questionnaires, which were analyzed using descriptive quantitative techniques through gain score and normalized gain (N-gain) calculations. The results showed significant improvement across all indicators, with the average pre-test score of 43.3% increasing to 91.7% in the post-test, while the N-gain was categorized as high. In addition to improving technical competence, the program also had a positive impact on teachers’ attitudes, self-confidence, and active participation in developing innovative learning media. The graphic novel media produced were considered pedagogically relevant and practically applicable in early childhood education. This program contributes to improving the quality of the learning process, strengthening the teacher learning community, and has the potential to be replicated in other early childhood education contexts.